Kook saam Kaaps : a study of language, positioning and food in the cooking show Flori en Koelsoem se kosse - Gallie, Tamsyn Keisha (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.